LEADER in the Czech Republic and farming sector - H. Hudečková; M. Lošťák (Agricultural Economics (AGRICECON), 2008)
The paper addresses the LEADER approach in the Czech Republic. Using documentary research and content analysis of the appropriate documents and the Local Action Groups information sheets, the paper firstly outlines the evolution of the LEADER approach in the Czech Republic (the paper points out the difference in understanding LEADER in the EU /focusing on capacity building and the use of intangible forms of capital/ and in the Czech Republic EU /focusing on investments/). The paper also analyses the participation of farmers and the farming related actors in the LEADER approach (approx. 30% of local action groups are composed by those actors, however, they mostly do not aim /similarly like non-farming actors/ at developing partnership but want to achieve the investments into production; that is why the Czech local action groups are rather quasi-partnerships; it is also reflected in a very low number of strategies aiming at the "adding value to local products" which is the closest to farmers /but it is the less opted theme: only 6% of projects/). The paper ends with the analysis of projects implemented under the LEADER scheme where the farmers participate. It shows that more than the integrated strategies, the Czech local action groups prefer the strategies of the multi-sector type. The paper also points out that the publicly available information about the activities of the local action groups is not sufficient, although the groups are funded from the public budgets. This fact makes the analysis more difficult as for the scientific merit but also contradicts the principles of democratic governance.